2022
DOI: 10.1021/jacs.2c02890
|View full text |Cite
|
Sign up to set email alerts
|

Sprayed Water Microdroplets Are Able to Generate Hydrogen Peroxide Spontaneously

Abstract: Ultrapure N2 gas was bubbled through water, and the humidified output containing undetectable concentrations of ozone filled a closed chamber in which 18 MΩ-cm water was sprayed through a silica capillary to form microdroplets. Analysis of the collected microdroplets by NMR spectroscopy showed the presence of hydrogen peroxide at a concentration level ranging from 0.3 to 1.5 μM depending on the flow conditions. This was confirmed using a spectrofluorometric assay. We suggest that this finding establishes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 19 publications
13
132
0
Order By: Relevance
“…Among the unique properties of water microdroplets, is the observation that water microdroplets form the highly reactive hydroxy radical OH⋅, which has been observed indirectly by using salicylic acid as a scavenger [5] . Another indirect observation is the detection of the recombination of hydroxyl radicals to form hydrogen peroxide (H 2 O 2 ) in water microdroplets [6–10] . The power of water microdroplets to promote redox chemistry unlike that found in bulk water has also been demonstrated in the reduction of dissolved chloroauric acid (HAuCl 4 ) in water microdroplets to yield gold nanoparticles and nanowires, [11] the reduction of doubly charged ethyl viologen (EV 2+ ) dissolved in water microdroplets to singly charged ethyl viologen (EV +.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Among the unique properties of water microdroplets, is the observation that water microdroplets form the highly reactive hydroxy radical OH⋅, which has been observed indirectly by using salicylic acid as a scavenger [5] . Another indirect observation is the detection of the recombination of hydroxyl radicals to form hydrogen peroxide (H 2 O 2 ) in water microdroplets [6–10] . The power of water microdroplets to promote redox chemistry unlike that found in bulk water has also been demonstrated in the reduction of dissolved chloroauric acid (HAuCl 4 ) in water microdroplets to yield gold nanoparticles and nanowires, [11] the reduction of doubly charged ethyl viologen (EV 2+ ) dissolved in water microdroplets to singly charged ethyl viologen (EV +.…”
Section: Figurementioning
confidence: 99%
“…[5] Another indirect observation is the detection of the recombination of hydroxyl radicals to form hydrogen peroxide (H 2 O 2 ) in water microdroplets. [6][7][8][9][10] The power of water microdroplets to promote redox chemistry unlike that found in bulk water has also been demonstrated in the reduction of dissolved chloroauric acid (HAuCl 4 ) in water microdroplets to yield gold nanoparticles and nanowires, [11] the reduction of doubly charged ethyl viologen (EV 2 + ) dissolved in water microdroplets to singly charged ethyl viologen (EV + * ), [12] and the formation of pyridyl anion and m-hydroxypyridine in spraying an aqueous solution containing dissolved pyridine to form microdroplets. [13] It is possible to generate OH * radicals by other means, such as by cavitation, [14] and by reactions of O 3 or O 2 at the microdroplet periphery.…”
mentioning
confidence: 99%
“…Microdroplet, an emerging class of chemical reactor, has attracted significant interests for chemical reactions acceleration by several orders of magnitude (10–10 6 ), probably because of the special air-water interface physicochemical properties ( Enami et al., 2014 ; Wei et al., 2020 ; Yan, 2021 ). In previous studies, the electrospray mass spectrometer is frequently employed for microdroplets generation, reaction and analysis ( Mehrgardi et al., 2022 ; Müller et al., 2012 ; Zhao et al., 2022 ). However, it is important to investigate the microdroplet chemistry at an individual droplet level to understand the mechanisms.…”
Section: Before You Beginmentioning
confidence: 99%
“…Microdroplet chemistry is of particular interest as a powerful system to promote chemical reactions that are difficult to carry out in bulk phases without the use of catalysts. Compared to bulk-phase-mediated reactions, microdroplet-mediated reactions can enhance the reaction rate drastically by factors of ≥10 3 . The first quantitative demonstration of accelerated chemical reaction rate in water microdroplets was reported by Lee and co-workers . Moreover, it has been observed that several unique reactions, such as spontaneous reduction of organic molecules and metal ions, , chemoselective N-alkylation of indoles, and generation of hydrogen peroxide (H 2 O 2 ), , can be effectively induced in micrometer-sized water droplets without catalysts while they scarcely appear in bulk aqueous solutions. These intriguing observations in the microdroplets are attributed to their interfacial properties, including the increase of the reaction rate constant in microcompartments and the high density and possible alignment of molecules near the droplet surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability of microdroplets to facilitate unusual chemical reactions, these reactions have been limited to the synthesis of low molecular weight compounds (molecular weight <1000 g/mol) at trace amounts of reactants (nM to μM). No study has yet demonstrated the utilization of microdroplets to generate high molecular weight polymer products at high reactant concentrations (mM to M).…”
Section: Introductionmentioning
confidence: 99%